Metal-organic frameworks-based mixed matrix pervaporation membranes for recovery of organics - Zehai Xu; Chao Liu; Lulu Xiao; Qin Meng; Guoliang Zhang (Advanced Membranes)
Metal-organic framework (MOF)-based mixed matrix membranes (MMMs) have attracted significant attentions for their distinguished characteristics in pervaporation such as enhanced selectivity, increased permeability and improved mechanical strength through the synergistic integration of polymeric matrices and inorganic fillers. Although many publications have emerged in recent years focusing on MOF-based MMMs, this review specifically emphasizes the improvement of MOF-based pervaporation membranes through the design of dimension of fillers and microstructure. The challenges encountered in MOF-based MMMs for pervaporation and the essential requirements for practical separation applications are addressed. A brief summary of strategies is provided for designing MOF-based MMMs with desired microstructure, macrostructure and multicomponent characteristics by using MOFs as fillers. The latest progresses in novel MOF-based MMMs with specific compositions, controllable pore structure and improved compatibility for recovery of organics are also displayed. The broad application prospects of MOF-based MMMs in pervaporation are introduced, including recovery of ethyl alcohol, butanol and other organics. Moreover, the challenges faced in the practical application of MOF-based MMMs for recovery of organics are presented and the promising future directions are outlined.